2022
DOI: 10.1101/2022.03.21.485171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicellular PI control for gene regulation in microbial consortia

Abstract: We describe two multicellular implementations of the classical P and PI feedback controllers for the regulation of gene expression in a target cell population. Specifically, we propose to distribute the proportional and integral actions over two different cellular populations in a microbial consortium comprising a third target population whose output needs to be regulated. By engineering communication among the different cellular populations via appropriate orthogonal quorum sensing molecules, we are able to c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The efficacy of this biomolecular mechanism has also been demonstrated experimentally in living cells, at both the cell population and the single-cell level, and in cell-free environments using either external (in silico) or embedded single-output control schemes [33,39,40,43,[55][56][57][58][59][60][61]. Furthermore, in recent years, considerable attention has been given to topologies combining the antithetic integral controller with proportional and derivative control action or biomolecular buffering [39,40,43,60,[62][63][64][65][66]. Such efforts seek to resolve commonly encountered issues associated with the standalone antithetic integral controller, such as instability, poor transient dynamics including overshoots, and long-lasting oscillations or increased variance.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of this biomolecular mechanism has also been demonstrated experimentally in living cells, at both the cell population and the single-cell level, and in cell-free environments using either external (in silico) or embedded single-output control schemes [33,39,40,43,[55][56][57][58][59][60][61]. Furthermore, in recent years, considerable attention has been given to topologies combining the antithetic integral controller with proportional and derivative control action or biomolecular buffering [39,40,43,60,[62][63][64][65][66]. Such efforts seek to resolve commonly encountered issues associated with the standalone antithetic integral controller, such as instability, poor transient dynamics including overshoots, and long-lasting oscillations or increased variance.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Integral (I) controllers are typically augmented with Proportional (P) and/or Derivative (D) controllers to obtain PI/PID controllers that offer more flexibility in enhancing the dynamic performance while maintaining the RPA property. Recently, more advanced molecular controllers such as PI/PID controllers found their way to molecular biology (7,(37)(38)(39)(40)(41)(42). Ideally, pure proportional control is achieved via instantaneous negative feedback from the output XL to the input species X1 and it is shown that it is not only capable of enhancing the transient dynamic performance, but also reducing cell-to-cell variability (37,40).…”
mentioning
confidence: 99%